Using heatmaps to identify opportunities for optimization of test utilization and care delivery - Yonah C Ziemba; Liya Lomsadze; Yehuda Jacobs; Tylis Y Chang; Nina Haghi (Elsevier, 2018)
Background: When a provider orders a test in a pattern that is substantially different than their peers, it may indicate confusion in the test name or inappropriate use of the test, which can be elucidated by initiating dialog between clinicians and the laboratory. However, the analysis of ordering patterns can be challenging. We propose a utilization index (UI) as a means to quantify utilization patterns for individual providers and demonstrate the use of heatmaps to identify opportunities for improvement. Materials and Methods: Laboratory test orders by all providers were extracted from the laboratory information system. Providers were grouped into cohorts based on the specialty and patient population. A UI was calculated for each provider's use of each test using the following formula: (UI = [provider volume of specific test/provider volume of all tests]/[cohort volume of specific test/cohort volume of all tests]). A heatmap was generated to compare each provider to their cohort. Results: This method identified several hot spots and was helpful in reducing confusion and overutilization. Conclusion: The UI is a useful measure of test ordering behavior, and heatmaps provide a clear visual illustration of the utilization indices. This information can be used to identify areas for improvement and initiate meaningful dialog with providers, which will ultimately bring improvement and reduction in costs. Our method is simple and uses resources that are widely available, making this method effective convenient for many other laboratories.